Single-nucleotide Fcγ receptor polymorphisms do not impact obinutuzumab/rituximab outcome in patients with lymphoma - Strefford, Jonathan C; Nowicka, Malgorzata; Hargreaves, Chantal E; Burton, Cathy; Davies, Andrew; Ganderton, Rosalind; Hiddemann, Wolfgang; Iriyama, Chisako; Klapper, Wolfram; Latham, Kate V; Martelli, Maurizio; Mir, Farheen; et al. (Blood advances, 2021)
Single-nucleotide polymorphisms (SNPs) have been shown to influence Fcγ receptor (FcγR) affinity and activity, but their effect on treatment response is unclear. We assessed their importance in the efficacy of obinutuzumab or rituximab combined with chemotherapy in untreated advanced follicular lymphoma (FL) and diffuse large B-cell lymphoma (DLBCL) in the GALLIUM (www.clinicaltrials.gov #NCT01332968) and GOYA (#NCT01287741) trials, respectively. Genomic DNA was extracted from patients enrolled in GALLIUM (n = 1202) and GOYA (n = 1418). Key germline SNPs, FCGR2A R131H (rs1801274), FCGR3A F158V (rs396991), and FCGR2B I232T (rs1050501), were genotyped and assessed for their impact on investigator-assessed progression-free survival (PFS). In both cohorts there was no prognostic effect of FCGR2A or FCGR3A. In FL, FCGR2B was associated with favorable PFS in univariate and multivariate analyses comparing I232T with I232I, with a more modest association for rituximab-treated (univariate: hazard ratio [HR], 0.78; 95% confidence interval [CI], 0.54-1.14; P = .21) vs obinutuzumab-treated patients (HR, 0.56; 95% CI, 0.34-0.91; P = .02). Comparing T232T with I232I, an association was found for obinutuzumab (univariate: HR, 2.76; 95% CI, 1.02-7.5; P = .0459). Neither observation retained significance after multiple-test adjustment. FCGR2B was associated with poorer PFS in multivariate analyses comparing T232T with I232I in rituximab- but not obinutuzumab-treated patients with DLBCL (HR, 4.40; 95% CI, 1.71-11.32; P = .002; multiple-test-adjusted P = .03); however, this genotype was rare (n = 13). This study shows that FcγR genotype is not associated with response to rituximab/obinutuzumab plus chemotherapy in treatment-naive patients with advanced FL or DLBCL.
Keywords: Rituximab; jednonukleotidový polymorfismus; Polymorphism, Single Nucleotide; protokoly protinádorové kombinované chemoterapie; receptory IgG; Antibodies, Monoclonal, Humanized; Humans; Receptors, IgG; lidé; humanizované monoklonální protilátky; rituximab; folikulární lymfom; Antineoplastic Combined Chemotherapy Protocols; Lymphoma, Follicular